Framing Teacher Education: An Analysis of the Comprehensive Educator Equity Plans of 16 State Education Agencies. Issue 1 (2nd January 2019) - Cuenca, Alexander; Nichols, Joseph R.
ABSTRACT: This article explores the nature of a federal intervention into teacher education through state policy making and problem framing. The authors examined the 16 comprehensive educator equity plans that were approved by the U.S. Department of Education in 2015 and surface four inadequacies the reports communicate about teacher education: (a) an inability to recruit diverse candidates, (b) an unsuitable curriculum for high-needs schools, (c) limited exposure to diverse teaching placements, and (d) an environment that lacks accountability. Through this project, this article covers how federal educational aims are delegated to states in order to frame economics as the goal of education and teacher education as negligent in this pursuit.